2018
DOI: 10.1111/cid.12676
|View full text |Cite
|
Sign up to set email alerts
|

Titanium as a modifier of the peri‐implant microbiome structure

Abstract: Background: Recent data support the implication of accelerated titanium dissolution products in peri-implantitis. It is unknown whether these dissolution products have an effect on the peri-implant microbiome, the target of existing peri-implantitis therapies. Purpose: This study assessed the relationship between the peri-implant microbiome, dissolved titanium levels, and peri-implantitis. Materials and methods: Clinical, microbiome, and titanium data were collected from a periodontal population having imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 56 publications
4
76
0
5
Order By: Relevance
“…with peri‐implantitis and healthy controls found an 8‐fold increase in titanium corrosion products in the plaque around implants with peri‐implantitis compared with healthy ones . In addition, when assessing the potential effects of titanium products on the peri‐implant microbiome using 16S rRNA analysis, titanium dissolution products have been shown to act as a modifier of the peri‐implant microbiome structure . These data support the utilization of treatment methods that prevent disruption of the titanium oxide surface.…”
Section: Interaction Between Biofilm and Titaniummentioning
confidence: 66%
“…with peri‐implantitis and healthy controls found an 8‐fold increase in titanium corrosion products in the plaque around implants with peri‐implantitis compared with healthy ones . In addition, when assessing the potential effects of titanium products on the peri‐implant microbiome using 16S rRNA analysis, titanium dissolution products have been shown to act as a modifier of the peri‐implant microbiome structure . These data support the utilization of treatment methods that prevent disruption of the titanium oxide surface.…”
Section: Interaction Between Biofilm and Titaniummentioning
confidence: 66%
“…In general, some studies revealed that the genera Streptococcus , Prevotella , and Haemophilus characterized peri‐implant health. Peri‐implantitis was associated with a marked increase in Veillonella . However, the generalizability of these findings in the oral mucosa to the skin is not clear, as oral mucosa is a tissue and microbial ecosystem with markedly contrasting characteristics to those of the skin.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, both periodontitis and peri‐implantitis are polymicrobial diseases, associated with a dysbiotic biofilm community. Peri‐implant microbiota may have distinct characteristics as compared to periodontal microbiota in both health and disease, owing to inherent differences in the environmental niche, and titanium exposure . Both diseases show a preponderance of anaerobic pathobiont species, which may be related to the severity of the disease .…”
Section: Discussionmentioning
confidence: 99%